2013
DOI: 10.1200/jco.2012.48.4691
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Investigation of Body Mass Index, Colorectal Adenoma, and Colorectal Cancer in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial

Abstract: A B S T R A C T PurposeObesity has consistently been linked to an increased risk of colorectal cancer, particularly among men. Whether body mass index (BMI) differentially influences the risk across the stages of colorectal cancer development remains unclear. We evaluated the associations of BMI with colorectal adenoma incidence, adenoma recurrence, and cancer in the context of a large screening trial, in which cases and controls had an equal chance for disease detection. MethodsWe prospectively evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 46 publications
3
53
0
1
Order By: Relevance
“…Similarly, Jacobs et al (60) reported an increased risk of adenoma recurrence over 3.1 years of follow-up among men (OR = 1.36; 95%CI: 1.01–1.83) without any association among women (OR = 0.90; 95%CI: 0.60–1.33). This was comparable to the report by Kitahara et al (61) using data from the Prostate, Lung, Colorectal and Ovarian (PLCO) screening Trial. The authors found a borderline increased risk of adenoma recurrence among men (OR, 1.50; 95% CI, 0.98 to 2.30) but not among women.…”
Section: Obesity and Adenomasupporting
confidence: 89%
“…Similarly, Jacobs et al (60) reported an increased risk of adenoma recurrence over 3.1 years of follow-up among men (OR = 1.36; 95%CI: 1.01–1.83) without any association among women (OR = 0.90; 95%CI: 0.60–1.33). This was comparable to the report by Kitahara et al (61) using data from the Prostate, Lung, Colorectal and Ovarian (PLCO) screening Trial. The authors found a borderline increased risk of adenoma recurrence among men (OR, 1.50; 95% CI, 0.98 to 2.30) but not among women.…”
Section: Obesity and Adenomasupporting
confidence: 89%
“…This is supported by previous publications that lower rates of CRC are associated with caloric restriction 29 and that the risk of colonic adenomas increases with increasing BMI. 24 It is possible that the reason there has not been a clearer relationship between obesity or BMI and CRC and its precursor lesions is because the relationship is non-linear, particularly in the most obese patients in our cohort. We did not recruit any patients with a BMI in excess of 46 kg/m 2 .…”
Section: Discussionmentioning
confidence: 94%
“…Western populations differ to Asian populations in several ways. Among them is the high rate of obesity and the metabolic syndrome, which have been associated with an increase in the risk of colonic adenomas 23,24 and CRC. [25][26][27][28] Conversely, caloric restriction and a low BMI may protect against developing cancer.…”
Section: Introductionmentioning
confidence: 99%
“…We were able to examine the specific components of birth weight—fetal growth and gestational age—while adjusting for potential confounders including maternal BMI and diabetes. Obese women deliver heavier babies on average (28, 29), and obesity is associated with a modestly increased risk of colorectal cancer (30), although this association has been more evident among men and is not consistently found among women (48, 49). Similarly, diabetic mothers also deliver heavier babies on average (29), and diabetes has been associated with a modestly increased risk of colorectal cancer (31).…”
Section: Discussionmentioning
confidence: 99%